From gangs to “mini-cárteles criollos”: drug dealing and evolution of criminal’s groups of Pavas - Saborío, Sebastián (2021)
Through 67 interviews to residents of Pavas, men deprived of liberty, and police authorities and after consulting journalistic material and official statistics, the researchers demonstrate that the practices of local criminal groups are transformed when they undertake drug-dealing activities. The authors state that the massive arrival of drugs to Pavas caused a raise in the use of violence for conflict resolution and increased the structuring of the criminal groups which transformed them from gangs to “criollo mini-cartels”, as defined by the authorities. The article analyzes the stages of the conflict among criminal groups and establishes relations among different aspects such as the socioeconomic characteristics of the context and the variety of actors involved in the struggles to control drug-selling and buying points.